Diseño de una metodología para realizar la transición del sistema de gestión de calidad con la NTC ISO 9001:2015 y propuesta de integración con el sistema de gestión de seguridad y salud ocupacional NTC OHSAS 18001:2007 para la empresa servicio aéreo medicalizado y fundamental S.A.S. Medicalfly S.A.S. (2017)
Medical and basic air service S.A.S. MedicalFly S.A.S. seeks to be a leading and competitive company in the field of air ambulances and also strengthen its services internationally to Central and South America and Caribbean Islands. In order to achieve this purpose, a methodology was designed to align and update the Quality Management System in accordance with requirements established in ISO 9001: 2015 and the model to be followed for the integration of Quality Management Systems And Occupational Safety and Health, in accordance with the requirements established in NTC ISO 9001-2015 and NTC OHSAS 18001-2007. The Project was carried out based on the analysis of the initial situation, independently reviewing compliance with the NTC ISO 9001: 2015 and NTC OHSAS 18001: 2007 standards, through a detailed review of the documentation in each process and interview with leaders thereof. The second stage of the project is established based on the result of the initial diagnosis, which allows the establishment of the actions for the integration proposal, and the models to be implemented according to the strategic direction of the company and the requirements of the standards Mentioned above. The result of the initial diagnosis made it possible to clearly identify the current situation in the company. The conclusion is that the current system fails, not integrating the common elements that each has. Being these independent, is generating reprocesses, lack of dynamism, commitment and interest on the part of the workers. Finally, it is important to highlight the advantages of the proposed methodology, allowing the integration of efforts and desires of each part of the system towards a common goal and obtaining excellence in work, which contributes to continuous improvement.